Services for Implementation of Cloud Technologies for Education - Christauskas, Česlovas; Misevičienė, Regina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In this paper, we analyzed the cloud computing technologies presenting overview of cloud computing models and possibilities of virtual infrastructure desktops and their benefits. We studied reduction of costs and savings of virtual desktops. Virtual desktops in Kaunas University of Technology we presented at the end.